An investigation into the waiting list experience : exploring parents' views of children referred to a Child and Adolescent Mental Health Service - Woodhouse, Wendy (University of Wolverhampton, 2007)
Aims: The purpose of the qualitative study was to gain insight into the way parents experience and manage the waiting process following a referral to a Child and Adolescent Mental Health Service. The aim was to use the information for future service delivery and therapeutic engagement. Method: 6 parents whose child had been referred to a Child and Adolescent Mental Health Service and had been waiting for more than eight weeks were recruited using a purposive sampling method and participated in a semi-structured interview. The interviews were transcribed and analysed using the principles of Pidgeon & Henwood’s (1992) grounded theory techniques, facilitating the development and refinement of a theoretical model. Results: The resulting model highlights the waiting experience as fraught by loneliness, abandonment and self blame resulting in an interchanging role of being active or passive and the subsequent cycle they subside into. Some parents use the waiting time effectively by searching for their own answers but may eventually become passive following a belief that their parenting is insufficient. The disempowerment and self blame that is perpetuated through waiting intensifies the parents’ helplessness and results in a wide disparity between a negative self view and the idealised view of the professional. Conclusion: This study described the difficult experiences parents face while waiting for their child’s initial appointment. Parents need to be offered support, information and empowerment while waiting with ongoing communication from the service. Recommendations for future service and clinical delivery are provided.